Applicability of the IRCA methodology in Peru, a literature review - Alvarez Ticllasuca, Adiel (2023)
Water is a fundamental need for human beings, however, it was not until 1958 that the "International Standards for Drinking Water" were created, establishing the parameters to indicate when water is for human consumption; later it underwent several modifications for its better understanding. In the case of Peru, the consumption of drinking water is a constitutional right by Law No. 30588, where 90.8% have access to the service, but most doubt its quality; On the other hand, the inhabitants who do not have it look for other sources, risking consuming water that does not meet the admissible parameters, thus affecting their health. Therefore, the objective of the study is to analyze the applicability of the IRCA methodology in Peru to improve drinking water quality standards. The type of approach of this research is descriptive to facilitate the deepening of the details of the subject to be treated. According to the results, there are several similarities regarding the analysis of the parameters between Resolution 2115 of 2007 and Supreme Decree No. 031-2010-SA. It is concluded that there is not enough information on the application of the IRCA methodology in Peru; however, its applicability is possible if said method is readjusted, mainly to indicate a minimum number of water samples analyzed so that it is statistically viable and the results are reliable.